Cross Cloud Computing in Security System - Gupta, Ankur; garg, Puneet (IJRDO -Journal of Computer Science Engineering, 2017)
Cloud Computing has been information technologies services on developed to deliver demand to organizations like as individual users, this technology is still in its early stages of development because it suffers from different security threats that prevent users trust it In this paper, we identify different security problems existing in cloud from several research papers & we show suggested solutions. This cross cloud represents next logical wave in computing, enabling complex hybrid applications, cost & performance optimization, enhanced reliability, customer flexibility & lock-in avoidance. Providing testing as a service in cross clouds become hot topics in industry.